The Relationship Between Parent’s Attention and Student's Learning Achievement in PAI Study at Elementary School - T. Idris; Adripen Adripen; Syafrinda Syafrinda (Al-Fikru: Jurnal Ilmiah, 2022)
This study aims to analyze the extent to which the relationship between parental attention and student achievement in Islamic Religious Education at SDN 11 Tanjung Barulak. This research is correlational quantitative research with sample in this study was taken using a proportionate stratified random sampling technique with 20 students. The data collection technique in this study used a questionnaire which was used to see whether or not there was a relationship between parental attention and student achievement in Islamic Religious Education subjects. The data analysis that the author did in this study was a product-moment correlation analysis. The results showed that the calculation of count show that the number obtained is 0.644 after a search with r-table at a significant level of 5% (0.443) r-count is greater than rtable (0.644 > 0.443) it can be interpreted that the relationship between parental attention and student achievement in subjects Islamic Religious Education at elementary school. This research also implies that the more attention paid by the parent, the higher the student learning achievement.